Extreme behavioural shifts by baboons exploiting risky, resource-rich, human-modified environments. Issue 1 (December 2017) - Fehlmann, Gaelle; O'Riain, M.; Kerr-Smith, Catherine; Hailes, Stephen; Luckman, Adrian; Shepard, Emily; King, Andrew
Abstract A range of species exploit anthropogenic food resources in behaviour known as 'raiding'. Such behavioural flexibility is considered a central component of a species' ability to cope with human-induced environmental changes. Here, we study the behavioural processes by which raiding male chacma baboons (Papio ursinus ) exploit the opportunities and mitigate the risks presented by raiding in the suburbs of Cape Town, South Africa. Ecological sampling and interviews conducted with 'rangers' (employed to manage the baboons' space use) revealed that baboons are at risk of being herded out of urban spaces that contain high-energy anthropogenic food sources. Baboon-attached motion/GPS tracking collars showed that raiding male baboons spent almost all of their time at the urban edge, engaging in short, high-activity forays into the urban space. Moreover, activity levels were increased where the likelihood of deterrence by rangers was greater. Overall, these raiding baboons display a time-activity balance that is drastically altered in comparison to individuals living in more remote regions. We suggest our methods can be used to obtain precise estimates of management impact for this and other species in conflict with people.